2018
DOI: 10.1186/s12906-018-2190-0
|View full text |Cite
|
Sign up to set email alerts
|

Profile of osteopathic practice in Spain: results from a standardized data collection study

Abstract: BackgroundThere is limited research regarding patients’ profiles and consumer attitudes and habits of osteopathy in Spain. The purpose of this study was to profile patients who regularly receive osteopathic care in Spain using an internationally developed standardized data collection tool.MethodDuring the period between April 2014 and December 2015, a UK-developed standardized data collection tool was distributed to Spanish osteopaths who voluntarily agreed to participate in this cross-sectional study.ResultsT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 46 publications
4
29
0
Order By: Relevance
“…In general, the typical osteopath in Spain is male, aged between 30-39 years, with a previous academic degree, mainly in physiotherapy, and part-time osteopathic education. These results are in line with the only previous study published in Spain [7], with the Benelux Osteosurvey [10] and the Italian OPERA version [16]. However, the latest 2011 KPMG Report profiling osteopaths [19] showed that UK osteopaths are older (41)(42)(43)(44)(45)(46)(47)(48)(49)(50).…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…In general, the typical osteopath in Spain is male, aged between 30-39 years, with a previous academic degree, mainly in physiotherapy, and part-time osteopathic education. These results are in line with the only previous study published in Spain [7], with the Benelux Osteosurvey [10] and the Italian OPERA version [16]. However, the latest 2011 KPMG Report profiling osteopaths [19] showed that UK osteopaths are older (41)(42)(43)(44)(45)(46)(47)(48)(49)(50).…”
Section: Discussionsupporting
confidence: 86%
“…Regular referrals are standard practice among Spanish respondents. However, patients in Spain mainly consult an osteopath through self-referral (Fig 4) in the pursuit of an alternative to previous unsuccessful treatments [7]. In this context it should be highlighted that interprofessional care is one of the ingredients for building effective modern health systems [24] and, although efforts have been made to promote interprofessional care within osteopathy, this interest should extend to research [25].…”
Section: Plos Onementioning
confidence: 99%
See 3 more Smart Citations